Air Tamponade for Rhegmatogenous Retinal Detachment With Inferior Breaks After 25-Gauge Pars Plana Vitrectomy: Technique and Outcome - Shen, Peiyang; Kong, Xiangbin; Zhou, Lijun; Su, Peng; Lu, Xiaohe; He, Mingguang (Frontiers in Medicine, 2022)
To evaluate the outcomes of 25-guage (G) pars plana vitrectomy (PPV) with air tamponade for rhegmatogenous retinal detachment (RRD) with inferior breaks. This retrospective consecutive case series included fifty-two eyes of fifty-two RRD patients with inferior breaks who underwent 25-G PPV with air tamponade. These patients were followed up for at least 6 months following surgery. Primary and final anatomical success rates and postoperative complications were the main outcome measures. The mean age of the patients (39 men and 13 women) was 51.8 ± 11.8 years. There were 49 primary RRDs (94.2%) and three recurrent RRDs (5.8%). The mean follow-up period was 8.2 ± 1.6 months (range: 6–13 months). Sixteen eyes (30.8%) presented with high myopia, and six eyes (11.5%) were pseudophakic. Proliferative vitreous retinopathy grade was C1 in four eyes (7.7%). Of the 52 eyes, two (3.8%) were complicated with choroidal detachment, and forty (76.9%) had the macula detached. The single- and final-operation success rates were 96.2% and 100%, respectively. During follow-up, secondary cataract surgery was performed in eight eyes (17.4%) of the 46 phakic eyes. 25-G PPV with air tamponade is effective in treating selected RRD patients with inferior breaks. Patients can benefit from early visual recovery and less complications.